Anodic Oxidative Disulfide Bond Formation in Egg Protein. Issue 11 (18th August 2016) - Takahashi, Masahito; Handa, Akihiro; Kodama, Risa; Chiba, Kazuhiro
Abstract: Oxidation of thiol groups and formation of disulfide bonds in food protein were achieved via an electrochemical reaction. Iodide acted as a redox mediator and effectively oxidized the thiol groups of the protein. The reaction mechanism was determined through cyclic voltammetry and indicated that indirect oxidation of the thiol group occurred. This anodic oxidation reaction was processed in a mediated fashion and allowed the oxidation of protein, a major macromolecule, without electron transfer involving direct interaction with the surface of the electrode. This reaction can be applied to concentrated ovalbumin or hen egg whites, indicating its usefulness for the food modification industry. Abstract :